PENGARUH PENAMBAHAN BUBUK BUNGA TELANG TERHADAP TOTAL BAL, ASAM LAKTAT, DAN pH KEFIR SUSU KAMBING - Usup Supriatna; Triana Setyawardani; Juni Sumarmono (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. Kefir has a yellow-white color and a complex nutritional profile. Based on this, the color and content of kefir can be increased for more attractive colors, and the phytochemical content of kefir can be increased by adding other elements. Butterfly pea (Clitoria ternatea) is an element that can be added to goat's milk kefir because it contains antibacterial substances. The purpose of this study was to investigate the effect of adding butterfly bean powder on the total amount of lactic acid bacteria, lactic acid content and pH value in goat milk kefir. Materials and Methods. In the production of goat milk kefir, 24 sample units were used with addition of 0%, 0.5%, 1%, 1.5%, 2% and 2.5% of butterfly pea powder (6 treatments and 4 replicates). The variables in this study were total lactic acid bacteria (log cfu/g), lactic acid level (%), and pH. Results. The effect of the addition of butterfly pea powder on the research variables was that it had no significant effect on total lactic acid bacteria, very significant effect on lactic acid levels, and very significant effect on pH. Total lactic acid bacteria of goat's milk kefir added with butterfly pea powder averaged 9.2±0.18 log cfu/ml to 9.4±0.45 log cfu/ml (P>0.05), lactic acid content had an average lactic acid level in the range of 1.97±0.29% to 3.00± 0.11% (P<0.01), and the pH values ​​had a mean range of 3.29±0.22 to 3.7±0.2 (P<0.01). Conclusion. The addition of butterfly pea powder with a percentage of 0.5% increased lactic acid levels and lowered the pH without inhibiting the growth of lactic acid bacteria.